Comparative Analysis of Occupant Thermal Comfort, Energy Consumption, and CO2 Emissions for an Educational Building in Cold Climate: A Case Study in Canada. Issue 1 (1st August 2022) - Mahmoud, S.; Saad, Mahmoud M.; Elshelfa, M.; Abdelkhalik, H.; Fahmy, M.
Abstract: Global climate change and global warming capture the attention of planners seeking more sustainable buildings to reduce dependence on fossil fuels and minimize energy consumption. Consequently, architects have developed buildings over the years and applied more sustainable strategies to cope with the environment, either in the shape of the building, the design of openings, or the use of more sustainable materials. These strategies provide more thermal comfort for long-term users. As a result, it is necessary to know the exact effect of using these strategies on thermal performance and energy consumption inside buildings. Therefore, researchers have developed many energy simulation tools and programs to provide a clear view of the nature of the building's thermal performance and energy consumption based on data inputs about local weather situations of the building. Thus, we must know the ability of the software to model different design strategies and be sure that the results are valid. This paper aims to make an environmental simulation of an educational building in Montreal, Canada, using Design-Builder simulation and compare it with the as-built equivalent thermal zones applying different glazing materials, which is the main element of the building facade to enhance the thermal comfort with the lowest energy consumption and CO2 emissions. This paper shows that using double glass low E 6/6mm Air gap is better for the case study building in cold climate weather that increases thermal comfort for the users, reduces energy consumption by 18.63%, and also reduces CO2 emissions by 18.57% per year.